Respuesta :

Answer:

x >>>>>>>> f(x)

–9 >>>>>> 10

–7 >>>>>>> 0

0 >>>>>>>> –35

5 >>>>>>>> –60

Step-by-step explanation:

f(x) = –5(x + 7)

1. x = –9, f(x) =?

f(x) = –5(x + 7)

f(x) = –5(–9 + 7)

f(x) = –5(–2)

f(x) = 10

2. f(x) = 0, x =?

f(x) = –5(x + 7)

0 = –5(x + 7)

Divide both side by –5

0 / –5 = x + 7

0 = x + 7

Collect like terms

x = 0 – 7

x = –7

3. x = 0, f(x) =?

f(x) = –5(0 + 7)

f(x) = –5(7)

f(x) = –35

4. f(x) = –60, x =?

f(x) = –5(x + 7)

–60 = –5(x + 7)

Divide both side by –5

–60 / –5 = x + 7

12 = x + 7

Collect like terms

x = 12 – 7

x = 5

SUMMARY:

x >>>>>>>> f(x)

–9 >>>>>> 10

–7 >>>>>>> 0

0 >>>>>>>> –35

5 >>>>>>>> –60